In vitro study of the effect of xylooligosaccharides obtained from banana pseudostem xylan by enzymatic hydrolysis on probiotic bacteria - de Freitas, Caroline [UNESP]; Terrone, Cárol Cabral [UNESP]; Masarin, Fernando [UNESP]; Carmona, Eleonora Cano [UNESP]; Brienzo, Michel [UNESP] (Elsevier, 2021)
Xylooligosaccharides (XOS) are xylose oligomers, recognized for their prebiotic effect, with the ability to impact health by influencing the gut microbiota. This study aimed to produce XOS by xylan enzymatic hydrolysis and evaluate the prebiotic effect. Endoxylanase was produced by Aspergillus versicolor and purified, and the xylan from banana pseudostem was alkali extracted. XOS production was performed through enzymatic hydrolysis by varying the parameters of xylanase load, substrate mass load, and reaction time. Lactobacillus plantarum and Lactobacillus fermentum were grown using XOS as a carbon source. Using an enzymatic load of 30 IU. g−1, it was possible to obtain a good amount of XOS and good yield, around 11 g.L−1, and 61%, respectively. Regarding the substrate concentration, the increase of concentration also increased XOS production, however, decreased the yield. There was not significant XOS production until 16 h and production was similar after 24 h. XOS with a higher degree of polymerization were mainly produced. Both probiotic bacteria were able to grow on XOS containing medium. Up to 48 h, the growth was similar, of 1010 CFU/mL, with glucose and XOS as the carbon source. The growth with XOS increased after 48 h, while the growth with glucose remained stationary. This study demonstrates that XOS from banana pseudostem xylan presents prebiotic properties by increasing probiotic bacteria growth.
Keywords: Enzymatic hydrolysis; Lactobacillus; Prebiotics; Xylanase; Xylooligossacharides